AIDS and Sacrifice: A Discussion of René Girard’s Scapegoat Theory of Sacrifice, Jean-Luc Nancy’s Unsacrificeable, and Giorgio Agamben’s Homo Sacer - Pump, Andrew (Université d'Ottawa | University of Ottawa, 2010)
This paper seeks to build upon René Girard’s scapegoat theory of sacrifice and group cohesion by considering post modern theories of sacrifice and society. It will explore the difficulty in applying a discourse of sacrifice when discussing contemporary political issues, or politically charged issues effecting minorities. By critically examining these theorists, I hope to distinguish between a religious theory of sacrifice and a modern theory explaining the relation of the ‘post-political’ subject to society and the state.